Integrated indices for sustainable water management in the Guanzhong Basin, China - Yong Wang; Yong Zhao; Xing Li; Long Yan; Wei Deng; Yuan Liu; Fan He; Jiaqi Zhai; Zhi Xu; Minjian Chen (Journal of Hydrology: Regional Studies)
Study Region: The alluvial fan area of the Guanzhong Basin, China. Study Focus: This study addresses the ecological flow requirements in rivers primarily fed by groundwater in alluvial fan areas, which are the transition zones between mountainous and plain regions, where the exchange of groundwater and surface water is particularly frequent. In many alluvial fan areas, excessive groundwater pumping drives declines in water tables, baseflow, and environmental streamflow. This study proposes two key concepts: ecological baseflow (EBF), defining the environmental flow threshold for ecosystem habitats, and ecological water table (EWT), representing the groundwater discharge threshold sustaining baseflow in alluvial fan areas. A method based on hydraulics and morphology is proposed to calculate these indices.New hydrological insights for the region: The results show that large-scale groundwater extraction in the alluvial fan area led to a significant decline in groundwater levels, resulting in reduced discharge to downstream rivers and even river depletion (i.e., rivers recharging groundwater). Consequently, the EBF could not be maintained. The findings of this study suggest an immediate reduction in groundwater extraction in the study area to restore the baseflow of downstream rivers and ensure the corresponding environmental flow of rivers in the region.